Basic Knowledges of Finite Element Method and Application in Implant Dentistry - Duangrattanaprathip, Nut; Rungsiyakull, Pimduen; Rungsiyakull, Chaiy; Suttiat, Kullapop (Chiang Mai Dental Journal, 2018)
Finite element analysis (FEA) is a mathematical technique which is the approximate model solutions of partial differentiate equations. This technique is not only commonly used in engineering, but also has been applied in several multidisciplinary sciences, including biomechanical investigation in dental materials and the distribution pattern of stress and strain that generated from oral function. This method is useful for improving in material design and studying the harmonization of material to living tissue. It is repeatable, low producing cost, comfortable to simulate and develop a positive end result. This literature explains and emphasizes on the basic knowledge of FEA, including FEA methodology, mechanical behaviors of the material and its application focusing in implant dentistry field.